1992
DOI: 10.1172/jci115962
|View full text |Cite
|
Sign up to set email alerts
|

Electroneutral K+/HCO3- cotransport in cells of medullary thick ascending limb of rat kidney.

Abstract: The renal medullary thick ascending limb (MTAL) of the rat absorbs bicarbonate through luminal H + secretion and basolateral HCO3 transport into the peritubular space. To characterize HCO3 transport, intracellular pH (pHi) was monitored by use of the pH-sensitive fluorescent probe (2',7')-bis-(carboxyethyl)-(5,6)-carboxyfluorescein in fresh suspensions of rat MTAL tubules. When cells were preincubated in HCO3 /C02-containing solutions and then abruptly diluted into HCO3/ C02-free media, the pHi response was an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
0

Year Published

1997
1997
2014
2014

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(20 citation statements)
references
References 27 publications
2
18
0
Order By: Relevance
“…These results do not confirm the absence of Cl Ϫ / HCO 3 Ϫ exchange described in rat MTALH suspensions (28). In contrast, they are in complete agreement with the results recently obtained in our laboratory using purified basolateral membrane vesicles from rat MTALH cells.…”
Section: Discussionsupporting
confidence: 49%
See 3 more Smart Citations
“…These results do not confirm the absence of Cl Ϫ / HCO 3 Ϫ exchange described in rat MTALH suspensions (28). In contrast, they are in complete agreement with the results recently obtained in our laboratory using purified basolateral membrane vesicles from rat MTALH cells.…”
Section: Discussionsupporting
confidence: 49%
“…Values for dpHi /dt were determined by a computer-assisted fitting of the pHi vs. time data to a linear regression line over the first [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] In the presence of 0.15 mM bath DIDS and in the basolateral presence of Cl Ϫ , pH i was not stable but steadily increasing (segment a-b, Fig. 1B), at variance with data obtained in the absence of peritubular DIDS (Fig.…”
Section: Methodsmentioning
confidence: 86%
See 2 more Smart Citations
“…The method used to isolate MTAL fragments has been previously described in detail (17,18). Because we have previously shown that glucocorticoids regulate BSC1 expression (19), MTAL fragments were harvested from rats that were adrenalectomized (ADX) and given isotonic saline as drink-ing water 6 d before the experiments to avoid any interference caused by endogenous glucocorticoids.…”
Section: Freshly Isolated Mtal Tubulesmentioning
confidence: 99%